Does community forestry management increase reforestation and sustainability? A comparative systematic review of studies in southeast Asia - Hardawati Yahya; Dayang Nur Sakinah Musa; M.N.F Sariee (Faculty of Science and Natural Resources, 2020)
The function of community forestry management in managing forest resources has been increased over the three decades. Numerous opportunities and outcomes are discussed; however, the benefits and implications of community forestry management in reforestation and sustainability of resources are still challenging and yet discovered. Therefore, this paper aims to compare different case studies of community forestry management in Southeast Asia in terms of implementation and implications of the program in reforestation and sustaining the forest resources. Using a systematic review and content analysis of the scholarly literatures in forestry particularly in community forestry management in Southeast Asia between 1994 – 2020, 134 relevant articles has been compiled and synthesised. This paper found that relatively few (48%) articles were adopted reforestation in community forestry management as tools to sustaining the forest resources. Moreover, this paper identified five categories of implications in terms of sustainability of reforestation in community forestry have been reported. This paper highlighted the need for reforestation as a tool to improve forest resources scarcity and the importance of stakeholder involvement in implementation and planning stages of community forestry management for further development.